2022
DOI: 10.3389/fpsyg.2022.820042
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Cognition and Practice of Educational Equity in English as a Foreign Language Teaching

Abstract: Teachers involved in English as a foreign language (EFL) teaching play a significant role in the process of moving toward educational equity. Teacher cognition is very influential in shaping teacher practice and thus affects students’ academic performance. However, although the role of EFL teachers as equity agents has been recognized, few studies have explored EFL teachers in-depth in terms of their cognition and practice. Moreover, no review studies have given sufficient attention to the task of elucidating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 72 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…Therefore, by borrowing Borg's (2003) term of teacher cognition which refers to the unobservable cognitive dimension of teaching -what teachers know, believe, and think, it can be assumed that there is strong evidence to suggest that teachers' experiences as learners can shape their cognitions about teaching and learning that continue to have an impact on them throughout their careers; there is also evidence to suggest that while professional preparation does shape teachers' cognitions, programs that disregard trainee teachers' prior beliefs may be less effective at influencing these; and research has also shown that teachers' experiences as learners can affect how they perceive teaching and learning (Borg, 2003). Furthermore, research has supported the claim that English Foreign Language (EFL) teachers' cognition can be very influential in shaping their instructional practices, thereby affecting the learning outcomes of the students (Chen & Abdullah, 2022). Taking the important part of beliefs to the teachers' cognition, so it is also necessary to consider the faculty members' belief of the EMI training course design.…”
Section: Literature Review Faculty Members' Belief In Emimentioning
confidence: 99%
“…Therefore, by borrowing Borg's (2003) term of teacher cognition which refers to the unobservable cognitive dimension of teaching -what teachers know, believe, and think, it can be assumed that there is strong evidence to suggest that teachers' experiences as learners can shape their cognitions about teaching and learning that continue to have an impact on them throughout their careers; there is also evidence to suggest that while professional preparation does shape teachers' cognitions, programs that disregard trainee teachers' prior beliefs may be less effective at influencing these; and research has also shown that teachers' experiences as learners can affect how they perceive teaching and learning (Borg, 2003). Furthermore, research has supported the claim that English Foreign Language (EFL) teachers' cognition can be very influential in shaping their instructional practices, thereby affecting the learning outcomes of the students (Chen & Abdullah, 2022). Taking the important part of beliefs to the teachers' cognition, so it is also necessary to consider the faculty members' belief of the EMI training course design.…”
Section: Literature Review Faculty Members' Belief In Emimentioning
confidence: 99%
“…At the micro level, as a result of inappropriate test-preparation practices, a test will also have negative effects on teaching and learning when students' scores increase without a concomitant increase in learning [36][37]. The other side of negative washback related to test-preparation practices is teaching to the test.…”
Section: Negative Washback Effectmentioning
confidence: 99%
“…3 Being compulsory in many non-English-speaking nations, English language teaching is seen as a primary communication medium in the global educational space. 4 In the context of prioritizing equity and excellence in education, as scholars 5 , 6 argue, English as a Foreign Language (EFL) teaching is strongly tied to the equity goal and thus exerts a substantial impact on the grand course of closing educational and social disparities. Therefore, primacy should be given to achieve equity in EFL teaching by creating a fair and inclusive learning environment where equal learning opportunities for all can be provided and diversified needs of students from different backgrounds can be fulfilled.…”
Section: Introductionmentioning
confidence: 99%
“…Since equity is a “moral obligation” in a society founded on democratic morality, 2 the intricate relationship between EFL teachers’ cognition and practices of equity deserves more scholarly attention. However, though there is a mounting number of studies focused on exploring EFL teachers’ equitable teaching in an ever-changing world within educational scope, little academic attention has been paid to illuminating the complexity of teacher cognition and practices from an equity lens 5 , 46 and there is still little agreement on what factors contribute to the cognition-practice inconsistency in the EFL teaching context. Therefore, in this study, an equity perspective is adopted as a response to the increasing attention on identifying the factors that constrain teachers’ equitable teaching in the EFL teaching context, calling for collective efforts to address these factors so that a more “democratic, participatory, equitable, professional, and egalitarian future” for all learners can be built.…”
Section: Introductionmentioning
confidence: 99%